Potent Antifouling Metabolites from Red Sea Organisms - S. Al-Lihaibi, Sultan; Abdel-Lateff, Ahmed; M. Alarif, Walied; Nogata, Yasuyuki; N. Ayyad, Seif-Eldin; Okino, Tatsufumi (Asian Journal of Chemistry, 2015)
Forty two marine macro-organisms include; algae, corals and sponges were collected from the Saudi Red Sea territorial water. The methanolic extracts of all the samples were evaluated towards their antifouling effects cyprid larvae of Balanus amphitrite. Fifteen crude extracts showed antifouling activity at 10 μg/mL, eleven of which considered to be promising for isolation targets from the results of low mortality. Two marine species of sponge Siphonochalina siphonella and red alga Laurencia obtusa were selected further chemical investigation.The extract of S. siphonella, was partially fractionated and led to isolation of two known triterpenoidal metabolites; sipholenol A (1) and sipholenone A (2). Three compounds; 2,10-dibromo-3-chloro-7-chamigrene (3) and 12-hydroxyisolaurene (4) and (12E)-cis-maneonene-E (5), were isolated from L. obtusa. All the compounds (1-5) were evaluated for their antifouling activities. Compounds 1, 3 and 4 showed potent effects with 48 h EC50, 0.2, 0.14 and 1.34 μg/mL, respectively. Compounds 1 and 3 were more potent than the positive control CuSO4 (EC50 = 0.34 μg/mL), while compound 2 showed moderate activity at 10 μg/mL.